Determination of nuclear charge radius by extreme-ultraviolet spectroscopy of Na-like ions - A. Hosier; Dipti; S. A. Blundell; A. Lapierre; R. Silwal; G. Gwinner; J. N. Tan; A. Naing; J. D. Gillaspy; Y. Yang; P. Szypryt; G. O'Neil; et al. (Physical Review Research)
We report on a method for determining the absolute nuclear charge radius of high-Z elements using extreme-ultraviolet spectroscopy of highly charged Na-like ions in tandem with highly accurate atomic structure calculations of transition energy differences. The application of this method has reduced the nuclear charge radius uncertainty of ^{191}Ir by a factor of 8 from the currently accepted literature value, with a recently reported charge radius of 5.442(12) fm. The result reduces the charge radius uncertainty along the full Ir isotopic chain when combined with prior optical isotope shift measurements. The technique utilizes only a few million ions stored in an ion trap, which should apply to measurements with small quantities of radioactive nuclei.